Variability of Near-Surface Salinity in the Nordic Seas Over the Past Three Decades (1991-2019) - Park, Ji-Eun; Kim, Hyun-Cheol; Cho, Kyoung-Ho (Frontiers in Marine Science, 2022)
Rapid climate change causes surface freshening and changes in the high latitude marine environment. The Nordic Seas have been widely implicated by deep water formation as a part of Atlantic Meridional Overturning Circulation. This study explores the spatiotemporal variations in the near-surface salinity over the Nordic Seas associated with surface freshening factors by using monthly TOPAZ4 reanalysis data from 1991 to 2019. We first show that reliability of TOPAZ4 data compared to the other salinity products of other reanalysis data, satellite data, and in-situ measurements in the Nordic Seas. The salinity variability was larger in the Greenland Sea (GS) than in the Norwegian Sea (NS) on both time scales of seasonal and interannual. The seasonal change of GS salinity was coincident with the seasonality of sea ice extent. The longer-time variations are decomposed by empirical orthogonal function (EOF) analysis. The GS salinity is mainly affected by current advection (29%), sea ice extent (11%). It is also partially affected by Greenland ice sheet discharge. The interannual response of salinity to the sea ice extent over the GS and land ice discharge differs by season. NS salinity variability responds to the strength of the Subpolar Gyre associated with a large-scale atmospheric system that caused the freshening event in the mid-1990s. The propagation of the northward Arctic Water core is observed over the period of about 3 years from the Faroe Shetland Channel to the Fram Strait at a speed of 2.6-6.5 year-1. Other freshening factors such as sea ice export from the Arctic, freshwater flux at the Fram Strait, and precipitation are also discussed. For the past three decades, the continuous trend appeared only in the sea ice extent and Greenland ice sheet discharge, which might be a signal of climate changes over high latitude. However, there was no significant trend other than the periodic change in a few years to the decadal time scale in the salinity of GS and NS. As preconditioning for deep convection, near-surface salinity within Greenland Sea Gyre was influenced by salinity fluctuation in both GS and NS, and the effect of land ice discharge was limited.